Meningkatkan Peluang ”Bisnis Digital Kewirausahaan” Di Era New Normal - Agnes Nogo Temu; Yuni Permata Sari (Jurnal Sultra Elementary School, 2020)
The development of online business is currently growing rapidly, as seen from the increasing number of people starting online ventures, ranging from product trading to selling digital content. This growth is inseparable from the influence of digital technology, which has changed people’s mindsets and ways of responding to life’s challenges. The COVID-19 pandemic has become a crucial moment that encouraged society to adapt by maintaining their economy through online business. This activity not only benefits entrepreneurs and distributors but also provides convenience for consumers in meeting their needs without leaving home. The decline in employment opportunities and limited mobility have driven people to become more creative and innovative, allowing them to use their time effectively and efficiently. This reality calls for collaboration between society and the government in optimizing digital business opportunities, including in regulatory aspects such as online business taxation. Therefore, synergy between both parties is essential to realize a shared vision of developing a sustainable digital economy.